Auditor rotation and audit quality : a thesis submitted in partial fulfilment of the requirements for the degree of Doctor of Philosophy at Massey University, Palmerston North, New Zealand - Uthayapong, Thanida (Massey University, 2020)
The thesis investigates the effect of mandatory audit partner rotation (MAPR) on audit quality of listed companies that underwent three rotation periods in the Thai capital market. MAPR is one of the requirements that regulators in many countries impose on auditors in order to enhance audit quality. The benefit of MAPR is in the incoming audit partner enhancing auditor independence and offering fresh insights to a client, which is expected to improve audit quality as evidenced by greater financial statements quality. On the other hand, the new lead audit partner can lack client-specific knowledge, which may impair audit quality. There are ongoing discussions about the benefits of MAPR in a number of countries but only a few studies have been conducted on the effects of MAPR in developing countries. This thesis therefore aims to fill this gap by examining the impact of MAPR on audit quality in a developing country, Thailand. This thesis is framed within the Agency Theory framework and also uses the IAASB (2014) framework for audit quality to identify the factors which have an impact on audit quality. A total of 417 firm-year observations between the years 2006 and 2017 are made of 286 non-financial Thai listed companies, all of which with experience of MAPR. The sample also includes multiple numbers of MAPR. The performance-matched discretionary accruals (DA) developed by Kothari, Leone, and Wasley (2005) are used to measure DA as a proxy for audit quality. The results in this thesis suggest that MAPR does not significantly improve audit quality and the relationship between MAPR and audit quality is weak. It is possible that an incoming lead audit partner lacks client-specific information, is disadvantaged by the gradual learning curve in understanding a client’s businesses, and may face challenges in communication within the audit team, all of which may not positively impact on audit quality. There is no strong evidence of an association between audit quality and other impacting factors, such as Big 4 audit firms, the audit firm industry specialist, the audit partner industry specialist, and the audit partner busyness. Results also present no evidence of significant improvement in audit quality in the first MAPR subsequent to voluntary rotation. However, MAPR does seem to improve audit quality under certain conditions, i.e. audit quality is improved depending on the number of rotation times, audit firm size and companies’/ clients’ size. Only listed companies with three MAPR audited by Big 4 audit firms and only larger listed companies with three MAPR have higher audit quality within the MAPR framework. Further, only listed companies with three MAPR that have a positive DA, are associated with higher audit quality. The overall results of this thesis suggest that MAPR requirement does not immediately lead to an improvement in audit quality, at least not in the Thai capital market.
Keywords: Auditing; Quality control; Auditors; Thailand; 350102 Auditing and accountability